2005
DOI: 10.1186/1472-6920-5-27
|View full text |Cite
|
Sign up to set email alerts
|

What motivates senior clinicians to teach medical students?

Abstract: Background: This study was designed to assess the motivations of senior medical clinicians to teach medical students. This understanding could improve the recruitment and retention of important clinical teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 11 publications
12
84
1
1
Order By: Relevance
“…[3][4][5][6] Studies in medical education examined motives and incentives to teach as well as the barriers encountered. [7][8][9][10][11][12][13][14][15][16][17][18][19] In the light of the recent trend towards more generalist teach-ing, most of these studies aimed at improving recruitment of (volunteer) community physicians. [8][9][10][11][12]14,15,17,19 The predominant qualitative research method used is the questionnaire survey, 7,[9][10][11][13][14][15][16]18,19 while focus groups 12 and semistructured interviews 17 are less frequently employed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Studies in medical education examined motives and incentives to teach as well as the barriers encountered. [7][8][9][10][11][12][13][14][15][16][17][18][19] In the light of the recent trend towards more generalist teach-ing, most of these studies aimed at improving recruitment of (volunteer) community physicians. [8][9][10][11][12]14,15,17,19 The predominant qualitative research method used is the questionnaire survey, 7,[9][10][11][13][14][15][16]18,19 while focus groups 12 and semistructured interviews 17 are less frequently employed.…”
Section: Introductionmentioning
confidence: 99%
“…From the scant literature available on the subject, the picture arises that both a feeling of responsibility for the training of future doctors and beliefs arising from the supervisors' achievement goal orientation play a role (Dahlstrom et al 2005;Dudek 2005;Cleveland et al 2007). This is in accordance with our finding that goal orientation is a main determinant of the assessment preference of both trainees and supervisors.…”
Section: Individual Perspective On Feedbackmentioning
confidence: 99%
“…So, what does motivate them? In a study of 75 senior clinicians from a variety of specialties, Dahlstrom et al [14] attempted to assess doctors' motivation to teach medical students. They reported that the main reasons for teaching amongst senior clinicians were altruistic.…”
Section: Motivating Medical Teachersmentioning
confidence: 99%